2002
DOI: 10.1046/j.1523-1755.2002.00273.x
|View full text |Cite
|
Sign up to set email alerts
|

ERK and p38 MAP kinase are required for rat renal development

Abstract: Both ERK and p38 are required for renal development. ERK appears to play a role in nephrogenesis and p38 for kidney growth and nephrogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
60
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 27 publications
4
60
1
Order By: Relevance
“…The role of JNK MAPK in embryogenesis has been investigated, and it has been shown that the loss of the MKK4 gene, a JNK activator, results in embryonic death (26). A decrease in glomerulus number was observed in 15-day-old embryos cultured for 48 and 120 h with ERK or p38 inhibitors (27). Choi et al (15) reported that the treatment of newborn rats with enalapril for 7 days increased JNK-2 and p38 MAPK expression in the kidney, and that these increases were temporally associated with higher numbers of apoptotic cells.…”
Section: Evidence For the Role Of Mapk In Kidney Developmentmentioning
confidence: 99%
“…The role of JNK MAPK in embryogenesis has been investigated, and it has been shown that the loss of the MKK4 gene, a JNK activator, results in embryonic death (26). A decrease in glomerulus number was observed in 15-day-old embryos cultured for 48 and 120 h with ERK or p38 inhibitors (27). Choi et al (15) reported that the treatment of newborn rats with enalapril for 7 days increased JNK-2 and p38 MAPK expression in the kidney, and that these increases were temporally associated with higher numbers of apoptotic cells.…”
Section: Evidence For the Role Of Mapk In Kidney Developmentmentioning
confidence: 99%
“…Among these, extracellular signal-regulated kinase (ERK) and p38 mitogen-activated protein kinase (p38) are required for nephrogenesis, metanephros growth, and ureteric bud branching (10)(11)(12). On the other hand, phosphatidylinositol 3-kinase (PI3K) and Akt, downstream signaling molecules of Ret, the kinase subunit of the glial cell line-derived neurotrophic factor (GDNF) receptor, promote branching morphogenesis (13).…”
mentioning
confidence: 99%
“…This is reminiscent of the metanephroi cultured with SB203580 in our previous study, in which WT1‐positive cells were distributed loosely in mesenchyme with slight signs of condensation around ureteric buds (Hida et al. 2002). Furthermore, SB203580‐treated metanephroi were small with reduced glomerular number.…”
Section: Discussionmentioning
confidence: 99%
“…These features are similar to metanephroi cultured with an inhibitor of p38 mitogen‐activated protein kinase (p38) as previously reported (Hida et al. 2002). BMP7 has been reported to be necessary for the maintenance of nephron progenitor cells through another member of MAP kinase c‐Jun N‐terminal kinase (JNK) (Blank et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation